Fuller Rose Beetle, Pantomorus cervinus (Boheman) (Insecta: Coleoptera: Curculionidae) - Jamba Gyeltshen; Amanda Hodges (EDIS, 2006)
EENY-375, a 5-page illustrated fact sheet by Jamba Gyeltshen and Amanda Hodges, describes this economically important pest of ornamentals and fruit. Part of the Featured Creatures series, this publication covers the synonymy, distribution, description, biology, host plants, damage, management, and selected references. Published by the UF Department of Entomology and Nematology, May 2006.